THE MEDIATING EFFECT OF JOB SATISFACTION ON THE RELATIONSHIP BETWEEN WORKPLACE SPIRITUALITY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Bismala, Lila; Handayani, Susi; Siregar, Gustina (Proceeding International Seminar of Islamic Studies, 2024)
Resources related to human capital are crucial to the organization. Naturally, as profit-driven businesses, small and medium-sized businesses must see human resources as critical to their entire success and as a key factor in boosting their competitiveness. Research on HR in SMEs is very important, because it can affect how SMEs will manage their human resources. With a sample of 175 employees who work in SMEs engaged in the culinary field, the researchers tested the mediating effect of the job satisfaction variable in the relationship between workplace spirituality and OCB. The results showed that job satisfaction did not mediate the relationship between workplace spirituality and OCB, because the direct influence of workplace spirituality on OCB was greater.